2016
DOI: 10.29313/ethos.v0i0.1687
|View full text |Cite
|
Sign up to set email alerts
|

Keanekaragaman Jenis Dan Sebaran Fagaceae Di Indonesia

Abstract: Fagaceae umumnya pohon, salah satu suku dengan jumlah jenis yang cukup besar ± 700 jenis di dunia tetapi sebagian besar tumbuh di belahan bumi utara. Di wilayah Malesia, ada lima marga yaitu Nothofagus, Castanopsis, Lithocarpus, Quercus dan Trigonobalanus dan jumlah jenis ± 180 dan sebagian besar di Indonesia tercatat 112 jenis. Penelitian ini dilakukan dengan studi literatur untuk menentukan keanekaragaman jenis Fagaceae di Indonesia serta distribusi dan pemanfaatannya. Fagaceae paling banyak tumbuh di Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…It can be assumed that the gap size of Leuwigoong is smaller than the rest of the location which affects light availability to promote the germination in this area as described in a previous study of the effect of gap size on regeneration of C. kawakamii is highly promoted by gap size, the larger gap size the higher regeneration rate (Buajan et al 2018). In general, Castanopsis growth cycle and diversity were influenced by the physical and chemical characteristics of the habitat as described by (Purwaningsih and Polosakan 2016;Chu et al 2020;He et al 2020). Castanopsis is well adapted in high altitude with high precipitation, a soil composition of 11.2% sand, 47.3% clay and 41.5% silt, 40% slope, and 60-97% relative humidity.…”
Section: Vegetation Analysis Of Cibodas Remnant Forestmentioning
confidence: 97%
See 2 more Smart Citations
“…It can be assumed that the gap size of Leuwigoong is smaller than the rest of the location which affects light availability to promote the germination in this area as described in a previous study of the effect of gap size on regeneration of C. kawakamii is highly promoted by gap size, the larger gap size the higher regeneration rate (Buajan et al 2018). In general, Castanopsis growth cycle and diversity were influenced by the physical and chemical characteristics of the habitat as described by (Purwaningsih and Polosakan 2016;Chu et al 2020;He et al 2020). Castanopsis is well adapted in high altitude with high precipitation, a soil composition of 11.2% sand, 47.3% clay and 41.5% silt, 40% slope, and 60-97% relative humidity.…”
Section: Vegetation Analysis Of Cibodas Remnant Forestmentioning
confidence: 97%
“…Previous studies revealed that Castanopsis species were distributed abundantly, especially in South China and the Indo-China region (Chen et al 2013;Cheuk and Fischer 2021). This genus has about 120 species in subtropical and tropical South Asia, 34 species in Malesia, and 24 species in Indonesia (Phengklai 2006;Purwaningsih and Polosakan 2016). Most of the genus Castanopsis is categorized as monoecious, evergreen and important taxa (Sun et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of low species richness is reflected also in a species-area curve. The speciesarea relationship is essential to ecology (Plotkin et al, 2000) and it can also be used to approximate species extinction resulting from habitat loss (May et al, 1995;Pimm & Raven, 2000) and to assess patterns of species diversity in different forest types (Ashton, 1965;Mueller-Dombois & Ellenberg, 1974, 2016. The curve was constructed to indicate species diversity in relation to the increasing size of the area (Mueller-Dombois & Ellenberg, 1974, 2016 within the plot.…”
Section: Species Compositionmentioning
confidence: 99%
“…Lauraceae, Fagaceae, and Euphorbiaceae are common families in the submontane forests (Steenis et al, 2006;Purwaningsih & Polosakan, 2016), hence, the forest is often designated as Lauro-Fagaceous forest (Steenis & Shippers-Lammertse, 1965;Steenis et al, 2006). In the present study, families in the submontane forest with a high number of species (> 5) were Lauraceae, Fagaceae, and Euphorbiaceae (Table 5).…”
Section: Species Compositionmentioning
confidence: 99%